Peningkatan kemampuan membaca puisi untuk anak SD Dusun Tawarsari - Tohani, Entoh; Destanti, Chrisvian (Universitas Negeri Yogyakarta, 2024)
Community Service Activities or commonly abbreviated as (PPM) is a form of means of applying the theory that has been obtained in higher education. PPM activities train students to develop social skills by being directly involved in society. This activity can also increase the human resource capacity of the community targeted by the activity. PPM activities with activities to improve the ability to read poetry for elementary school children in Tawarsari Hamlet. The implementation of this PPM uses limited observation methods, analysis of community needs, preparation of work programs and activity plans, determination of time allocation for work program consultations, and limited socialization. This program is carried out with poetry learning activities, namely writing poetry, practicing poetry reading, and poetry reading video competitions. Overall, the implementation of the PPM work program can run well. The community responded well to the program run by students.